Performa Burung Puyuh Jantan Coturnix-cortunix japonica) yang Diberi Tepung Daun Binahong (Anredera cordifolia (Ten) Steenis) dalam Pakan (Universitas Djuanda Bogor, 2022)
Quail (Coturnix coturnix japonica) is one of the poultry commodities that has a bright role and prospects for producing eggs. This study aims to examine the effect of supplementary feeding in the form of binahong leaf meal in feed on the growth performance of male quail. This research was conducted in January - February 2020 at the Gunung Gede Cage, the Vocational School of the Bogor Agricultural University, located in Gunung Gede, Bogor City, West Java. The materials used in this study were 100 male quail aged 10 days. This study used a completely randomized design (CRD) consisting of 4 treatments and 5 replications. The treatments in this study were R0 = 0% binahong leaf flour R1 = 0.5% binahong leaf flour, R2 = 1% binahong leaf flour, 1.5% binahong leaf flour. The data obtained were analyzed using Analysis of variance (ANOVA), if the data showed significantly different results (P <0.05) followed by the Duncan test. The variables observed in this study were feed consumption, body weight gain, feed conversion, and mortality. The results of this study indicated that giving binahong leaf meal in feed had a significant effect on feed consumption and had no significant effect on body weight gain, ration conversion and mortality on the growth period of quails. The conclusion of this research is that giving binahong leaf meal in feed up to a level of 1.5% has no effect on the performance of male quail.